2022
DOI: 10.1039/d2ob00254j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,3-diselenyl-dihydroisobenzofurans via electrochemical radical selenylation with substituted o-divinylbenzenes and diselenides

Abstract: An efficient electrochemical method for the direct synthesis of complicated 1,3-diselenyl-dihydroisobenzofuran was developed under an external oxidant free condition at room temperature from substituted o-divinylbenzenes and diselenides. A radical mechanism...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…1,3-Dihydroisobenzofurans (phthalanes) widely exist in many natural products, biologically active molecules and pharmaceuticals. 70 In 2022, Liu et al described an electrochemical radical selenylation with substituted o -divinylbenzenes and diselenides toward the formation of two C–Se bonds and two C–O bonds (Scheme 56), 71 which enables the efficient construction of 1,3-diselenyl-dihydroisobenzofurans in the presence of LiBF 4 as the electrolyte under a constant current of 6 mA. Control experiments indicated that the reaction proceeds through a radical pathway.…”
Section: Oxychalcogenation Of Alkenes and Alkynesmentioning
confidence: 99%
“…1,3-Dihydroisobenzofurans (phthalanes) widely exist in many natural products, biologically active molecules and pharmaceuticals. 70 In 2022, Liu et al described an electrochemical radical selenylation with substituted o -divinylbenzenes and diselenides toward the formation of two C–Se bonds and two C–O bonds (Scheme 56), 71 which enables the efficient construction of 1,3-diselenyl-dihydroisobenzofurans in the presence of LiBF 4 as the electrolyte under a constant current of 6 mA. Control experiments indicated that the reaction proceeds through a radical pathway.…”
Section: Oxychalcogenation Of Alkenes and Alkynesmentioning
confidence: 99%
“…In this methodology, seleno-dihydroisobenzofurans 18 were prepared by an initial formation of the organoselenyl radical species, which add to the carbon-carbon double bond forming the benzyl alcohol. [48] The benzyl alcohol behaves as a nucleophile attacking the intermediate carbocation I to give the products (Scheme 21). The improvement of this reaction is the introduction of the two portions of diorganyl diselenides (one R 1 SeSeR 1 gives two R 1 Se) into the final structure of the product.…”
Section: Organoseleno Cyclization Reactions Of Alkenesmentioning
confidence: 99%
“…Benzyl alcohols, prepared in situ by anodic oxidation of alkenes, are excellent nucleophiles in the organoseleno cyclization of ortho ‐divinylbenzenes. In this methodology, seleno‐dihydroisobenzofurans 18 were prepared by an initial formation of the organoselenyl radical species, which add to the carbon‐carbon double bond forming the benzyl alcohol [48] . The benzyl alcohol behaves as a nucleophile attacking the intermediate carbocation I to give the products (Scheme 21).…”
Section: Diorganyl Diselenides Promoting Cyclization Reactionsmentioning
confidence: 99%
“…In 2022, Liu and co-workers extended this protocol to synthesize complex 1,3-diselenyl-dihydroisobenzofurans through radical oxyselenenylation of substituted o -divinylbenzenes (Scheme 28). 75 The optimum reaction conditions involved a constant-current electrolysis at 6 mA using a Pt plate anode and cathode in an undivided cell containing a mixed electrolyte solution of LiBF 4 in CH 3 CN and H 2 O (800 : 1).…”
Section: Intramolecular Selenofunctionalizationmentioning
confidence: 99%